Conformational twisting of a formate-bridged diiridium complex enables catalytic formic acid dehydrogenation. Issue 38 (12th September 2018) - Lauridsen, Paul J.; Lu, Zhiyao; Celaje, Jeff J. A.; Kedzie, Elyse A.; Williams, Travis J.
Abstract : Catalytic reactivity is switched on for formic acid dehydrogenation by a single precursor's unique ability to form a geometrically twisted dimer. Abstract : We previously reported that iridium complex1a enables the first homogeneous catalytic dehydrogenation of neat formic acid and enjoys unusual stability through millions of turnovers. Binuclear iridium hydride species5a, which features a provocative C 2 -symmetric geometry, was isolated from the reaction as a catalyst resting state. By synthesizing and carefully examining the catalytic initiation of a series of analogues to1a, we establish here a strong correlation between the formation of C2-twisted iridium dimers analogous to5a and the reactivity of formic acid dehydrogenation: an efficient C2 twist appears unique to1a and essential to catalytic reactivity.